When social media becomes medicine: clinician-moderated online consultations as an informal healthcare access point - Inna Bleicher; Maya Peled-Raz; Sun Bleicher; Sharon Tzemah (Israel Journal of Health Policy Research, 2026)
Abstract Background Social media has evolved significantly as a platform for healthcare communication, education, and consultation, especially following the COVID-19 pandemic. While these platforms are increasingly used for medical advice, they operate largely outside formal health policy frameworks, creating a growing “informal layer” of healthcare. Methods A cross-sectional observational study was conducted using an anonymous online questionnaire distributed to the “ Ask an M.D .” group members from April to July 2023. Demographic characteristics, consultation patterns, motivations for using the platform, and comparisons between users from central and peripheral regions of Israel were analyzed, to identify potential disparities in digital health access. Results Of approximately 19,000 members who viewed the survey, 1,508 responded (8%). Respondents were predominantly female (85%), with a mean age of 38.5 years, and 61.5% reported higher education. Common reasons for using the group included seeking a second opinion (36%), delays in obtaining a doctor’s appointment (34%), and urgent health concerns (28%). Consultation topics most often involved gynecology and obstetrics (19%), pediatrics (15%), and dermatology (10.5%). Peripheral respondents were underrepresented relative to their proportion in the wider population. Within the respondent sample, central and peripheral participants showed broadly similar reported patterns of platform use. Conclusions Clinician-moderated social media groups such as “Ask an M.D.” may serve as a supplementary source of health information and informal consultation for some users, particularly when immediate formal care is less accessible. The lower representation of peripheral respondents in this survey should be interpreted cautiously and may reflect differences in survey exposure, response propensity, platform reach, or other factors. Because this study did not assess clinical outcomes, it cannot determine whether participation in the platform improves care, safety, or health equity.